1992
DOI: 10.1246/cl.1992.1917
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Sideroxylonals from Eucalyptus sideroxylon

Abstract: The structures of two novel isopentyl phloroglucinol dimers, designated as sideroxylonals A and B were deduced on the basis of proton magnetic resonance, 13C-nuclear magnetic resonance and mass spectral evidences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 3 publications
3
31
0
Order By: Relevance
“…Spectroscopic data for sideroxylonal C (3) strongly indicated that it was an isomer of the previously described sideroxylonal A (1) and B (2). 2 In the mass spectrum, the compound exhibits a characteristic retro-Diels Alder fragmentation with a strong fragment at m/z 250 and a weak M +• at m/z 500. The m/z 250 ion further fragments with loss of a C 4 H 7 fragment to give another characteristic ion at m/z 195.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopic data for sideroxylonal C (3) strongly indicated that it was an isomer of the previously described sideroxylonal A (1) and B (2). 2 In the mass spectrum, the compound exhibits a characteristic retro-Diels Alder fragmentation with a strong fragment at m/z 250 and a weak M +• at m/z 500. The m/z 250 ion further fragments with loss of a C 4 H 7 fragment to give another characteristic ion at m/z 195.…”
Section: Resultsmentioning
confidence: 99%
“…Sideroxylonal C (3) was isolated as a white powder from the 10% ethanol/hexane extract of the leaves of Eucalyptus melliodora in a 0•024% yield. The extraction solvent was removed and after chromatography and recrystallization a mixture of sideroxylonals B (2) and C (3) (c. 30 : 70) was obtained. Sideroxylonal B (2) was removed by washing the mixture with dichloromethane to give pure sideroxylonal C (3).…”
Section: Resultsmentioning
confidence: 99%
“…Formylated phloroglucinols have also proved to be therapeutically and/or pharmacologically significant (EBV inhibitory (Takasaki et al 1990), anti-bacterial (Satoh et al 1992), HIV-RT inhibitory (Nishizawa et al 1992), aldose reductase inhibitory (Satoh et al 1992), anti-protozoal (Bharate et al 2006. The dimeric derivative, sideroxylonal A, has proved to act as a potent marine anti-fouling agent comparable to the most active compound 2,5,6-tribromo-1-methyl-gramine (Singh et al 1996).…”
Section: Potential Usesmentioning
confidence: 99%
“…inhibitors of the human plasminogen activation (Neve et al, 25 1999) and antibacterial compounds (Satoh et al, 1992). carpals have antibacterial properties against dermatophytes 27 cariogenic and periodonthopathic bacteria (Osawa et al, 1996) 28 and seem to stimulate the synthesis of ceramides in corneum 29…”
mentioning
confidence: 99%